Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3892/mmr.2020.10915
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of chemerin and therapeutic efficacy of chemerin‑9 in pancreatogenic diabetes mellitus

Abstract: chemerin is a novel adipokine that regulates immune responses, adipocyte differentiation, and glucose metabolism. However, the role of chemerin in pancreatogenic diabetes mellitus (PdM) remains unknown. PdM is recognized as dM occurring secondary to chronic pancreatitis or pancreatic resection due to the loss of the loss of islet cell mass. The aim of the present study was to investigate the role of chemerin in PdM by collecting blooding samples from dM patients and establishing in vivo PdM model. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
5
2
Order By: Relevance
“…Finally, we examined the effects of chemerin-9 on the expression of chemerin and CMKLR1. Results showed that the circulating chemerin and the AAA-tissue chemerin/CMKLR1 expression were downregulated following the chemerin-9 treatment, contradicting previous studies [ 24 , 52 ]. These conflicts may be attributed to the different dosages or modes of chemerin-9 administration, or the disparate microenvironment of experimental models.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Finally, we examined the effects of chemerin-9 on the expression of chemerin and CMKLR1. Results showed that the circulating chemerin and the AAA-tissue chemerin/CMKLR1 expression were downregulated following the chemerin-9 treatment, contradicting previous studies [ 24 , 52 ]. These conflicts may be attributed to the different dosages or modes of chemerin-9 administration, or the disparate microenvironment of experimental models.…”
Section: Discussioncontrasting
confidence: 79%
“…Chemerin-9, an analog of chemerin, has a higher affinity for CMKLR1 and functions as an anti-inflammatory regulator to inhibit the development of atherosclerosis, Alzheimer's disease, and pancreatogenic diabetes [22][23][24]. However, the role of chemerin-9 in the biological behavior of AAA has so far been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest that chemerin and its agonistic derivatives hold considerable potential for treating, e.g., pancreatic diabetes mellitus, 33 cancer, 34 or impaired wound healing. 35 Therefore, the cyclic peptide presented here could directly be a valuable therapeutic tool.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Moreover, chemerin was identified as a novel adipokine to regulate adipocyte metabolism [ 11 ]. In addition, chemerin has been implicated to play an important role in the pathogenesis of obesity as well as diabetes [ 12 17 ]. As a chemoattractant, adipocyte-secreted chemerin was associated with insulin resistance [ 18 ].…”
Section: Discussionmentioning
confidence: 99%